2017
DOI: 10.1021/acsami.7b05335
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Colorimetric Sensor for Moisture Detection in Organic Solvents and Application in Inkless Writing

Abstract: Colorimetric sensors based on Sudan-III (1) and Alizarin red S (2) have been developed for the detection of a trace amount of water in organic solvents such as THF, acetone, acetonitrile, and DMSO. The deprotonated (anionic) forms of 1 and 2 namely 1.F and 2.F are reprotonated by using a trace amount of water. Deprotonation of 1 and 2 was obtained by using fluoride anion. Test papers of 1.F and 2.F in organic solvents with and without moisture showed dramatic changes in color. Receptor 1.F exhibits high sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…98 To date, they have been successfully used for water-soluble color humidity sensors, [99][100][101][102][103][104][105][106][107][108] sweat hole mapping systems, [109][110][111][112][113] water detection in organic solvents, [114][115][116][117] and rewritable paper. 44,46,54,97,98,111,[118][119][120][121] Particularly, hydrochromic materials are very popular in the design of water-jet printing rewritable papers. This is because water is clean, low cost, convenient, and compatible with current inkjet printers.…”
Section: Hydrochromic Materials For Green Printingmentioning
confidence: 99%
“…98 To date, they have been successfully used for water-soluble color humidity sensors, [99][100][101][102][103][104][105][106][107][108] sweat hole mapping systems, [109][110][111][112][113] water detection in organic solvents, [114][115][116][117] and rewritable paper. 44,46,54,97,98,111,[118][119][120][121] Particularly, hydrochromic materials are very popular in the design of water-jet printing rewritable papers. This is because water is clean, low cost, convenient, and compatible with current inkjet printers.…”
Section: Hydrochromic Materials For Green Printingmentioning
confidence: 99%
“…Several strategies have been demonstrated to meet the requirement, such as intramolecular charge transfer (ICT), [5][6][7][8][9] excited state intramolecular proton transfer (ESIPT), [9][10][11] photo-induced electron transfer (PET), [12][13][14][15][16][17][18] aggregation-induced emission (AIE), 7,29,30 decoloration of hydrogen-bonding photochromic dyes, 31 and other water-triggered mechanisms. [19][20][21][22][23][24][25][26][27][28] Generally, in each system, there is a specic range of water concentration available for detection; AIE is observed in high water concentrations, 7,29,30 whereas other systems exhibit optical changes in a relatively low concentration range. In this context, a reasonable approach to incorporating two mechanisms into one sensor molecule has been developed to detect and determine water in organic solvent sensitively in a wide concentration range, including the combinations of ICT or PET and AIE, [32][33][34][35][36][37][38][39] two water-induced reactions, 40 and two ICT-related mechanisms, 41,…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kumar et al . utilized dye‐fluoride complex for the colorimetric detection of water in THF (LOD=0.0058 wt % ) and acetone (LOD=0.0042 wt %) through protonation and deprotonation . The same research group also reported dye‐fluoride complex for water signalling in acetonitrile (LOD=0.0011 wt %) and THF (LOD=0.0026 wt %) .…”
Section: Resultsmentioning
confidence: 99%